Design and simulation of series loaded resonant converter: article / Aizatul Azlin Ghazali - Ghazali, Aizatul Azlin (2010)
In this paper, design techniques and simulation of the series loaded resonant converter operating above resonance are presented. The half-bridge series loaded resonant topology is considered in this paper. This converter had been designed based on 100 kHz switching frequency with variation of input voltage of 50K ± 20%. From the voltage conversion ratio, curve, the desired natural frequency, a>0 can be determined by approximate the value of w n which is 1.1. The value of resonant frequency f o can be determined. The result shows that the tank circuit (L and Q is maintained in the continuous conduction mode which gives sinusoidal waveform. Detailed circuit simulation is carried out using PSIM simulation package to verify the circuit operation.